Resíduos Sólidos de Construção Civil: análise, desafios e perspectivas em Montes Claros/MG - Bruna Andrade Ferreira (2019)
One of the great problems observed in the companies refers to the production of the solid residues, generated from the intense process of growth of the cities. The issue of waste has been discussed for some decades in the national and international spheres, denoting the expansion of collective awareness regarding the environment. The 2010 National Solid Waste Policy (PNRS) is a great tool to mitigate the impacts of solid waste. Thus, this work addresses the problem of urban solid waste generated by the construction sector. In this context, the general objective was to analyze the municipal public management process for the disposal of solid waste from civil construction in the urban context of Montes Claros-MG. For that, the process of urbanization and space production was approached, contextualizing Montes Claros-MG; the guidelines of the National Solid Waste Policy and its effectiveness were examined; and, the processes of management of Civil Construction Waste in Montes Claros, mapping the places of destination of these materials were analyzed. In order to reach the proposed objectives, the research methodology articulated three dimensions: a) bibliographic research; b) documentary research; c) field research, with the application of interviews and questionnaires to agents involved in the management of solid construction waste in the municipality. It is considered that the process of institutionalization of solid waste management in the city of Montes Claros, based on the PNRS, is only incipient.